2020
DOI: 10.1007/s11104-020-04671-5
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the aetiology of kiwifruit decline: interaction between soil-borne pathogens and waterlogging

Abstract: Aims In 2012, Italian kiwifruit orchards were hit by a serious root disease of unknown aetiology (kiwifruit decline, KD) that still causes extensive damage to the sector. While waterlogging was soon observed to be associated with its outbreak, the putative role of soil microbiota remains unknown. This work investigates the role of these two factors in the onset of the disease. Methods Historical rainfall data were analysed to identify changes that might explain KD outbreak and mimic the flooding conditions r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
41
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 41 publications
3
41
0
Order By: Relevance
“…P. chamaehyphon strain KD-15 from FVG (ITS region sequence under the accession number MN535819; Savian et al 2020a), further identified based on sequencing the LSU and COI regions (accession numbers MW431329 and MW430118), was selected for the pathogenicity test.…”
Section: Amentioning
confidence: 99%
See 4 more Smart Citations
“…P. chamaehyphon strain KD-15 from FVG (ITS region sequence under the accession number MN535819; Savian et al 2020a), further identified based on sequencing the LSU and COI regions (accession numbers MW431329 and MW430118), was selected for the pathogenicity test.…”
Section: Amentioning
confidence: 99%
“…Both trials were kept in a greenhouse at 28±5°C. After transplanting, water content was maintained proximal to field capacity for 3 weeks for trial 1 and 4 weeks for trial 2, before applying three rounds of flooding and drainage to induce symptoms (Savian et al 2020a). Wilting appearance was recorded after 25, 35, and 50 days post inoculation (dpi) in trial 1 and every 2-3 days in trial 2.…”
Section: Amentioning
confidence: 99%
See 3 more Smart Citations